Analysing organisational life: Haslam, A (2000) Psychology in organisations: The social identity approach. London Sage. ISBN 0-7619-6158-5 pbk. 432 pages. - Stott, Clifford (PINS-Psychology in Society, 2026)
Psychology in organisations: A social identity approach by Alex Haslam is well written, systematically structured and comprehensive. Yet it is a highly readable, accessible and powerfully argued text. The book, written by one of the pre-eminent theorists in the social identity tradition, provides a social psychological (re)analysis of• organisational life. It is a book that challenges many of the central assumptions, and exposes the implicit political implications, of the dominant theoretical models in the field of organisational psychology. In this sense alone it is a controversial and worthwhile read for those with an interest in organisational and social psychology, human behaviour in organisational contexts and the politics of organisational theory.